(3Jbhje GdHdOGf GdeUQjIs
(3BNQgG (B:s
(3gPG BNQ GdCbGdje HGdOjGQ GdeUQjI s
(3GdHdOGf GdeUQjI ceG cGfJ ai GjGe Gdedc GdCTQa TYHGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B23 - (3U (B561 s
(3eUOQ GbJfGA GdCUd (B:s
(3ceHQOL (B(65 - o 9) s
Keywords: (3GdLZQGajG h GdHdOGfs